Acute Pain Medicine in the United States: A Status Report. Issue 9 (10th June 2015) - Tighe, Patrick; Buckenmaier, Chester C.; Boezaart, Andre P.; Carr, Daniel B.; Clark, Laura L.; Herring, Andrew A.; Kent, Michael; Mackey, Sean; Mariano, Edward R.; Polomano, Rosemary C.; Reisfield, Gary M.
Abstract: Background: Consensus indicates that a comprehensive, multimodal, holistic approach is foundational to the practice of acute pain medicine (APM), but lack of uniform, evidence‐based clinical pathways leads to undesirable variability throughout U. S. healthcare systems. Acute pain studies are inconsistently synthesized to guide educational programs. Advanced practice techniques involving regional anesthesia assume the presence of a physician‐led, multidisciplinary acute pain service, which is often unavailable or inconsistently applied. This heterogeneity of educational and organizational standards may result in unnecessary patient pain and escalation of healthcare costs. Methods: A multidisciplinary panel was nominated through the APM Shared Interest Group of the American Academy of Pain Medicine. The panel met in Chicago, IL, in July 2014, to identify gaps and set priorities in APM research and education. Results: The panel identified three areas of critical need: 1) an open‐source acute pain data registry and clinical support tool to inform clinical decision making and resource allocation and to enhance research efforts; 2) a strong professional APM identity as an accredited subspecialty; and 3) educational goals targeted toward third‐party payers, hospital administrators, and other key stakeholders to convey the importance of APM. Conclusion: This report is the first step in a 3‐year initiative aimed at creating conditions and incentives for the optimal provision of APM services to facilitate and enhance the quality of patient recovery after surgery, illness, or trauma. The ultimate goal is to reduce the conversion of acute pain to the debilitating disease of chronic pain.